Experimental Study Of The Effects Of Egg Yolk Oil (Eyo) On Emulsified Biofuel Properties And Compression Ignition (Ci) Engine Performance Improvement - Zulbakri, Mohammad Luqman (Universiti Sains Malaysia, 2021)
There is a rise of interest among researchers in applying biofuel in compression-ignition (CI) engine due its wide availability locally. However, the direct use of biofuel into CI engine has led to many problems to the engine mainly due to its high viscosity than baseline diesel fuel. The problems include longer penetration, poor atomisation, poor combustion, carbon deposits in the cylinder, wear, and tear. To reduce the viscosity of biofuel, a proper blending known as emulsification of biofuel, require surfactant and water. Commercial surfactants such as Span80 and TritonX series are commonly used in the emulsification of biofuel to reduce its surface tension but in terms of cost, they are very expensive. In this project, an affordable egg yolk oil (EYO) has been explored and introduced to the emulsification of biofuel to reduce the consumption of the surfactants. The EYO addition into the emulsified biofuel (EB) was varied from 5%, to 30% by volume, with an increment of 5%. The effects of EYO addition to the emulsified biofuel properties, spraying characteristics and engine performance were studied. The results show that the increase of EYO addition by % composition reduces the viscosity and calorific value of EB whereas the density increases. The spray pattern of EBEYO depicted a significant reduction of the penetration length and increasing cone angle, thus, signifying a better atomisation of the fuel. Based on the engine performance test using EBEYO, the exhaust temperature reduces with the increase of EYO addition. Even though it is feasible, the torque and brake power performances are lower than the baseline diesel.